2021
DOI: 10.1177/1971400921998941
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings of cutaneous angiosarcoma of the scalp: Comparison with cutaneous squamous cell carcinoma

Abstract: Purpose This study aimed to evaluate imaging findings of cutaneous angiosarcoma (cAS) of the scalp compared with those of cutaneous squamous cell carcinoma (cSCC). Methods This study included 15 patients with primary cAS and 10 with primary cSCC of the scalp. Seven patients with cAS and eight with cSCC underwent magnetic resonance imaging, and 11 patients with cAS and eight with cSCC underwent 18F-fluorodeoxyglucose–positron emission tomography/computed tomography imaging. Imaging findings for both pathologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This was in keeping with height measurements for scalp SCC as measured on MRI in a similar study. 33 Using the limits of agreement method, it can be seen that the results of thickness assessment on CT are consistent with histological thickness at the 95% level. One possible explanation for the high correlation is the small cohort size and high variability in thickness measurements taken (SD = 7.3 mm on CT and 6.5 mm on histology).…”
Section: Discussionmentioning
confidence: 79%
“…This was in keeping with height measurements for scalp SCC as measured on MRI in a similar study. 33 Using the limits of agreement method, it can be seen that the results of thickness assessment on CT are consistent with histological thickness at the 95% level. One possible explanation for the high correlation is the small cohort size and high variability in thickness measurements taken (SD = 7.3 mm on CT and 6.5 mm on histology).…”
Section: Discussionmentioning
confidence: 79%
“…Unlike TCs and PTTs, cutaneous angiosarcoma appears as a flat elevated lesion with invasion of subcutaneous fat tissue. 24 There are several limitations to this study. First, this was retrospective study with a small sample size from a single institution.…”
Section: Discussionmentioning
confidence: 94%
“…3 Cutaneous squamous cell carcinoma exhibits a flattened configuration, superficial ulceration, protrusion and ill-demarcated deep margins. 23,24 Cutaneous angiosarcoma also occurs predominantly on the scalp and demonstrates hypointensity on T2-weighted images similar to TCs. Unlike TCs and PTTs, cutaneous angiosarcoma appears as a flat elevated lesion with invasion of subcutaneous fat tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggested a malignant cutaneous and likely sarcoma, for which FDG PET/CT was performed for staging. [1][2][3][4][5][6] The maximum intensity projection (MIP) image (A) showed a solitary intense activity in the right shoulder (arrow). On the axial images of the shoulders (B: PET, C: CT, D: fusion), the activity (arrow) was in the posterior right shoulder with maximum standardized uptake value (SUVmax) of 18.3 in comparison to hepatic SUVmax of 2.8, which corresponded to a lobulated soft tissue mass about 5.2 Â 3.4 Â 3.7 cm (arrow) without adjacent muscle or bone involvement.…”
mentioning
confidence: 99%
“…An MRI scan of the right shoulder (images not shown) from an outside institution reported that the mass was T1 isointense, T2 hyperintense to muscle with diffusion restriction and significant enhancement on postcontrast images. The findings suggested a malignant cutaneous lesion and likely sarcoma, for which FDG PET/CT was performed for staging 1–6 . The maximum intensity projection (MIP) image ( A ) showed a solitary intense activity in the right shoulder (arrow).…”
mentioning
confidence: 99%